1320 Evaluation of Routine Group and Save Testing Prior To Appendicectomy. (12th October 2021) - Fadel, M; Patel, I; Brewer, J; Behar, N
Abstract: Introduction: Group and save (G&S) testing is often performed prior to emergency appendicectomy. However, there are no standard national guidelines regarding the routine use of preoperative G&S. We performed a Trust Audit to review the need for G&S prior to appendicectomy in order to recommend new guidelines. Method: Retrospective review of all patients that underwent appendicectomy at Chelsea and Westminster Hospital between October 2019 and March 2020. We evaluated the existing literature on blood transfusion rate and the need for G&S prior to appendicectomy. Results: One hundred and seventy-three patients (female 56%, median age 26 years) underwent appendicectomy (94% laparoscopic, 6% open). One hundred and thirty-four (77%) patients had a valid G&S and none of the patients received a blood transfusion perioperatively. The estimated total cost of G&S sampling for laparoscopic appendicectomy over one year in the Trust is £6825 (excluding all other laparoscopic surgery). Conclusions: Based on the audit findings and literature review, routine G&S testing is not necessarily required for all patients undergoing laparoscopic appendicectomy. G&S should be requested on a patient case-specific basis (for example, chronic anaemia or haematological conditions) with discussions between the anaesthetist and surgeon. This would reduce delays in emergency lists, have financial implications and there is no evidence to support that the routine use of G&S benefits patient outcomes. These recommended guidelines have been presented at Surgery/Anaesthetics Clinical Governance and have been rolled out in the Trust with the aim to perform a re-audit in 3-6 months.